Retracted: Observations on radiological correction of acetabular dysplasia by Dega transiliac osteotomy - Jan, Wazir Fahad; Sarup, Sanjay; Dar, Mohd Yahya; Jahan, Alamgir; Khan, Ovais Nazir (International Journal of Research in Medical Sciences, 2017)
The article titled, "Observations on radiological correction of acetabular dysplasia by Dega transiliac osteotomy", published in the International Journal of Research in Medical Sciences, Volume 5, Issue 5, 2017, Pages 1991-1997, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20171831 is being retracted on authors request. The authors of this article want to redo the calculations with a follow up of more than 4 years so that the results are more conclusive of the effectiveness of the procedures. Since majority of patients are of developmental dysplasia of hip (DDH) the results are not representative of the effectiveness of the procedure in other disorders associated with acetabular dysplasia. Either the study has to be restricted to the patients of DDH or need to add more patients from other pathologies to make it a more conclusive study regarding other causes of acetabular dysplasia. The authors want to add some more criteria for assessment of acetabular dysplasia so that the effectiveness of the procedure can be gauged in a better way.